2004
DOI: 10.1111/j.1744-7429.2004.tb00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in the Relative Abundance of Fruit Bats (Megachiroptera: Pteropodidae) in Relation to the Availability of Food in a Lowland Malaysian Rain Forest

Abstract: The aims of this study were to investigate the diet and relative abundance of fruit bats in a lowland Malaysian rain forest and to test the hypothesis that the local assemblage structure of fruit bats varies significantly over time in relation to the availability of food. In total, 352 fruit bats of eight species were captured during 72,306 m2 mist‐net hours of sampling between February 1996 and September 1999. Three species of fruit bats (Balionycteris maculita, Chironax melanocephalus, and Cynopterus brachyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 19 publications
2
50
0
5
Order By: Relevance
“…Parry-Jones and Augee (2001) and Williams et al (2006) investigated food resources and the effect of food availability on the occupation of urban areas by P. poliocephalus in Australia, where Richards (1990) also described the diet of P. conspicillatus. Bumrungsri et al (2007) reported on the diet of two species of Cynopterus in Thailand, and Hodgkison et al (2003Hodgkison et al ( , 2004 studied nine fruit bat species in Peninsular Malaysia.…”
Section: Decoy Cropsmentioning
confidence: 99%
“…Parry-Jones and Augee (2001) and Williams et al (2006) investigated food resources and the effect of food availability on the occupation of urban areas by P. poliocephalus in Australia, where Richards (1990) also described the diet of P. conspicillatus. Bumrungsri et al (2007) reported on the diet of two species of Cynopterus in Thailand, and Hodgkison et al (2003Hodgkison et al ( , 2004 studied nine fruit bat species in Peninsular Malaysia.…”
Section: Decoy Cropsmentioning
confidence: 99%
“…Indeed, apart from a few studies in the Philippines (Reiter & Curio, 2001; Mildenstein et al, 2005; Stier & Mildenstein, 2005), Thailand (Weber et al, 2015), and Myanmar (Win & Mya, 2015), all other dietary and foraging studies on Southeast Asian Pteropodidae have focused on the smaller pteropodids (e.g., Hodgkison et al, 2004; Fletcher, Zubaid & Kunz, 2012; Bumrungsri et al, 2013; Stewart, Makowsky & Dudash, 2014). This is of particular concern given that out of the 67 flying fox species listed on the IUCN Red List, almost half (30 species i.e., 45%) are found in Southeast Asia (IUCN, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Absence of correlation between fruit availability and fruit bat captures may be due to the continuous fruit availability provided by Ficus luschnathiana (Table 4). Although food availability influences bat species composition (Hodgkison et al 2004) and reproduction (Mello et al 2004b), fructification of Ficus species provide food throughout the year and can explain why there was no obvious seasonality in the captures of fruit bats.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the abundance and species composition of frugivorous bats are related to food availability (Hodgkison et al 2004). Species that feed on fruits available throughout the year are captured continually while species which forage on temporary resources are found intermittently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation